Impact of COVID-19 pandemic on Vascular Surgery Unit activity in Central Romania - Emil-Marian, Arbănași; Reka, Kaller; Vasile Adrian, Mureșan; Septimiu, Voidăzan; Eliza-Mihaela, Arbănași; Eliza, Russu (Frontiers in Surgery, 2022)
The COVID-19 outbreak has placed substantial pressure on the medical systems worldwide. This study aimed to investigate the influence of the prepandemic vs. pandemic period on the activity of the Vascular Surgery Unit of a large emergency hospital in Eastern Europe. We performed a retrospective review of the vascular surgery cases admitted, comparing the statistics from the two time periods. We examined data of a total of 1,693 patients over the two periods. We report a 34.51% decrease in the surgical procedures performed during the pandemic period, with a disproportionate 80.6% decrease in the number of cases admitted with a diagnosis of venous insufficiency diagnosis and an increase of 67.21% in the number of patients admitted with acute arterial ischemia. Furthermore, individuals not classed as emergencies were delayed or denied surgical care. The number of nonurgent procedures conducted by our Vascular Surgery Unit decreased significantly, whereas the number of emergency surgeries increased. COVID-19′s effect is projected to have a long-term impact on how surgical treatments are provided in Romania.